Human epididymis protein 4 aggravates airway inflammation and remodeling in chronic obstructive pulmonary disease - Yuan Zhan; Jinkun Chen; Jixing Wu; Yiya Gu; Qian Huang; Zhesong Deng; Shanshan Chen; Xiaojie Wu; Yongman Lv; Zhilin Zeng; Jungang Xie (Respiratory Research, 2022)
Abstract Background Chronic obstructive pulmonary disease (COPD) is a progressive disease characterized by chronic inflammation and airway remodeling. Human epididymis protein 4 (HE4) plays a critical role in various inflammatory or fibrotic diseases. However, the role of HE4 in COPD remains unidentified. Methods HE4 expression was determined in the lung tissues from COPD patients and cigarette smoke (CS)-exposed mice using immunohistochemical staining, qPCR, or western blot. The plasma level of HE4 was detected by ELISA. The regulations of HE4 in the expressions of CS extract (CSE)-induced inflammatory cytokines in human bronchial epithelial cells (HBE) were investigated through knockdown or overexpression of HE4. The role of secretory HE4 (sHE4) in the differentiation and proliferation in human pulmonary fibroblast cells (HPF) was explored via qPCR, western blot, CCK8 assay or 5-ethynyl-2′-deoxyuridine (EdU) staining. The probe of related mechanism in CSE-induced HE4 increase in HBE was conducted by administrating N-acetylcysteine (NAC). Results HE4 was up-regulated in both the lung tissue and plasma of COPD patients relative to controls, and the plasma HE4 was negatively associated with lung function in COPD patients. The same enhanced HE4 expression was verified in CS-exposed mice and CSE-induced HBE, but CSE failed to increase HE4 expression in HPF. In vitro experiments showed that reducing HE4 expression in HBE alleviated CSE-induced IL-6 release while overexpressing HE4 facilitated IL-6 expression, mechanistically through affecting phosphorylation of NFκB-p65, whereas intervening HE4 expression had no distinctive influence on IL-8 secretion. Furthermore, we confirmed that sHE4 promoted fibroblast-myofibroblast transition, as indicated by promoting the expression of fibronectin, collagen I and α-SMA via phosphorylation of Smad2. EdU staining and CCK-8 assay demonstrated the pro-proliferative role of sHE4 in HPF, which was further confirmed by enhanced expression of survivin and PCNA. Pretreatment of NAC in CSE or H2O2-induced HBE mitigated HE4 expression. Conclusions Our study indicates that HE4 may participate in airway inflammation and remodeling of COPD. Cigarette smoke enhances HE4 expression and secretion in bronchial epithelium mediated by oxidative stress. Increased HE4 promotes IL-6 release in HBE via phosphorylation of NFκB-p65, and sHE4 promotes fibroblastic differentiation and proliferation.